Implementing Sets to Solve Economic Example Cases Through Mathematic Approach - Oktavianty Oktavianty (PT FORMOSA CENDEKIA GLOBAL, 2023)
The ability of students to solve mathematical problems is the focus of this study work, which investigates the relationship between students' grasp of high-level mathematics and their ability to do so. The purpose of this study is to investigate the difficulties that students experience when attempting to learn and apply mathematical concepts, specifically in the context of set operations. The ability to solve problems was evaluated by observing and testing a representative subset of the student population. The findings call attention to the significance of fostering mathematical proficiency in students and point to the necessity of establishing instructional methods that strengthen students' ability to solve problems.The ability of students to solve mathematical problems is the focus of this study work, which investigates the relationship between students' grasp of high-level mathematics and their ability to do so. The purpose of this study is to investigate the difficulties that students experience when attempting to learn and apply mathematical concepts, specifically in the context of set operations. The ability to solve problems was evaluated by observing and testing a representative subset of the student population. The findings call attention to the significance of fostering mathematical proficiency in students and point to the necessity of establishing instructional methods that strengthen students' ability to solve problems.